Basic microeconomics - Baumol, William J.; Blinder, Alan S.; Solow, John L. (Singapore : Cengage Learning Asia Pte Ltd, 2022)
Economics is a broad-ranging discipline, both in the questions it asks and the methods it uses to seek answer. Many of the world's most pressing problems are economic in nature. The first part of this chapter gives you some idea of the sorts of issues that economic analysis helps to clarify and the kinds of solutions that economic principles suggest. The second part briefly introduces some tools that economist use. You are likely to find some of these tools useful in your career, personal life, and role as an informed citizen, long after this course is over.
Chapter 1. What is Economics? -- Chapter 2. The Fundamental Economic Problem: Scarcity and choice -- Chapter 3. Supply and Demand An Initial Look -- Chapter 4. Consumer Choice: Individual and Market Demand -- Chapter 5. Demand and Elasticity -- Chapter 6. Output, Price and Profit: The Importance of Marginal Analysis -- Chapter 7. The Firm and the industry under perfect competition -- Chapter 8. The case for free markets: the price system -- Chapter 9. Monopoly -- Chapter 10. Between competition and monopoly -- Chapter 11. Taxation and Resource Allocation -- Chapter 12. Pricing the factors of Production -- Chapter 13. Labor and Enterpreneurship: The Human Inputs -- Chapter 14. International Trade and Comparative Advantage.
Includes bibliographical references and index.
Keywords: MICROECONOMICS